Meta-Analysis and Evaluation by Insect-Mediated Baiting Reveal Different Patterns of Hypocrealean Entomopathogenic Fungi in the Soils From Two Regions of China - Masoudi, Abolfazl; Wang, Min; Zhang, Xiaoli; Wang, Can; Qiu, Zhaoxi; Wang, Wenying; Wang, Hui; Liu, Jingze (Frontiers in Microbiology, 2020)
A survey was carried out on forest soils and grassland soils from Hebei and Sichuan provinces using Tenebrio molitor larvae as a bait, and high-throughput DNA sequencing (HTS) of the fungal internal transcribed spacer-2 ribosomal DNA was used to monitor the natural distribution of three leading hypocrealean families of insect fungal pathogens (Clavicipitaceae, Cordycipitaceae, and Ophiocordycipitaceae). The occurrence of insect fungal pathogens in soil samples from 98 different sites was compared. The use of insect bait indicated that entomopathogenic fungi of the genus Metarhizium were predominant, followed by Beauveria and Isaria. Molecular characterization using the Mz_FG543 intergenic region revealed that the Metarhizium species pool was phylogenetically composed of three closely related species as follows; Metarhizium pingshaense (n = 74), Metarhizium robertsii (n = 51), and Metarhizium brunneum (n = 26), as well as one isolate which clustered with Metarhizium flavoviride. Nine potentially new phylogenetic species were delimited within the M. flavoviride species complex by sequencing of the 5′ elongation factor-1 alpha region locus. The Beauveria (n = 64) and Isaria (n = 5) isolates were characterized via sequence analyses of the Bloc region. An intergenic spacer phylogeny of the Beauveria isolate assemblage revealed the phylogenetic species within the Beauveria bassiana clade. Interestingly, the individuals of M. pingshaense (n = 18) and M. brunneum (n = 12) exhibited the presence of both mating types in Sichuan Province. Similarly, for the Beauveria isolates, reproductive mode assays demonstrated that all four B. bassiana subclades possessed bipolar outcrossing mating systems. Of these, 19 isolates contained two mating types, and the rest were fixed for single mating types, revealing opportunities for intra-lineage heterothallic mating. The HTS results showed a significantly higher occurrence of the Clavicipitaceae family and the Metarhizium genus in the soil samples. The Venn diagram showed Metarhizium anisopliae (senso lato), Isaria farinose, and B. bassiana as frequently abundant fungal pathogen operational taxonomic units (core) across sampling sites, while the baiting method showed that the genus of Isaria was isolated locally. The Mantel test verified that community dissimilarity increased significantly with geographical distance, suggesting that geographical coordinates are possible factors that influence the insect fungal pathogen community composition in the studied sites. This study is the first to highlight the usefulness of utilizing soil baiting and deep sequencing to investigate the population dynamics of entomopathogens in soil.